2017
DOI: 10.1371/journal.pone.0176573
|View full text |Cite
|
Sign up to set email alerts
|

The functional microbiome of arthropods

Abstract: Many studies on the microbiome of animals have been reported but a comprehensive analysis is lacking. Here we present a meta-analysis on the microbiomes of arthropods and their terrestrial habitat, focusing on the functional profile of bacterial communities derived from metabolic traits that are essential for microbial life. We report a detailed analysis of probably the largest set of biochemically defined functional traits ever examined in microbiome studies. This work deals with the phylum proteobacteria, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 84 publications
(370 reference statements)
7
82
0
Order By: Relevance
“…These are interesting observations considering the hypothesis of environmentally‐ and diet‐derived colonization of the gut microbiome. In addition to humans, in which perinatal factors are believed to play an important role in microbiome seeding (Dominguez‐Bello et al, ), other organisms are reported to have significant seeding from the habitat they live in, including marine organisms (Chen, Chen, Weng, Shaw, & Wang, ), birds (Wu et al, ), and soil‐dwelling arthropods (Degli Esposti & Martinez Romero, ).…”
Section: Discussionmentioning
confidence: 99%
“…These are interesting observations considering the hypothesis of environmentally‐ and diet‐derived colonization of the gut microbiome. In addition to humans, in which perinatal factors are believed to play an important role in microbiome seeding (Dominguez‐Bello et al, ), other organisms are reported to have significant seeding from the habitat they live in, including marine organisms (Chen, Chen, Weng, Shaw, & Wang, ), birds (Wu et al, ), and soil‐dwelling arthropods (Degli Esposti & Martinez Romero, ).…”
Section: Discussionmentioning
confidence: 99%
“…In a review Bouchon et al (2016) synthesized current knowledge about the terrestrial microbe of isopods and identified future directions to understand the functional role of symbiotic bacteria. Esposti and Romero (2017) showed the phylum proteobacteria, which is usually dominant in marine and terrestrial environments and covers all functions associated with microbiomes.…”
Section: Identification Of Sequenced 16s Rdna Fragments From Dggementioning
confidence: 99%
“…Recent efforts are mapping the microbiome of Earth for different habitat types (see for instance the Earth Microbiome project 1 and the Global Ocean Microbiome project 2 ), however, the connection between environment and population microbiome is still lacking and difficult to predict. While it is true that consistent efforts have been devoted to the analysis of diseaseor symptom-specific alterations of the microbiome in relation to external environmental agents (Bucci et al, 2012;Davenport et al, 2017;Karkman et al, 2017;Mitmesser and Combs, 2017), a large gap exists in the analysis of how the spatiotemporal distribution of microbiota in the environment [e.g., soils (Jansson and Hofmockel, 2018), plants (Wackett, 2019), water (Lee et al, 2016), and natural hosts (Bahrndorff et al, 2016;Degli Esposti and Martinez Romero, 2017)] affects the microbiome in natural and human communities. Note that this ecological investigation, guided by theory, targeted monitoring and models (see section "Pattern-Oriented Models"), does not necessarily need to focus on health but on any spatio-temporal pattern manifesting ecological states of co-evolving microbiomes such as biodiversity patterns [see Parfrey and Knight (2012) and Ochman et al (Moeller et al, 2016b;Ochman, 2016)] and other socio-ecological ecosystem services.…”
Section: Human -Environment-microbiome Nexusmentioning
confidence: 99%